1993
DOI: 10.1159/000261573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glass-Ionomer Cement on Carious Dentine: An in vivo Study

Abstract: The effect of a glass-ionomer cement sealant on carious dentine was investigated clinically and bacteriologically. The study group consisted of 24 molar teeth, with small clinical visible occlusal dentine lesions, in 13 children (aged 7–18 years). Twenty of these molars were filled and sealed with a glass-ionomer cement (Fuji Ionomer Type III®) and 4 with a resin sealant (Delton®). From each molar, two dentine samples were collected aseptically with a time interval of 7 months. The first sample was taken after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 8 publications
2
42
0
4
Order By: Relevance
“…Concerning the GIC, its antimicrobial effect, mainly attributed to the fluoride release, probably contributed significantly to arrest caries progression [Benelli et al, 1993;Weerheijm et al, 1993;Bertacchini et al, 1999;Francci et al, 1999]. On the other hand, its physicochemical bonding to dentin could have inhibited bacterial percolation through the tooth/restoration interface [Dionysopoulos et al, 1994;ten Cate and van Duinen, 1995;ten Cate et al, 1995;Mertz-Fairhurst et al, 1995;Francci et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the GIC, its antimicrobial effect, mainly attributed to the fluoride release, probably contributed significantly to arrest caries progression [Benelli et al, 1993;Weerheijm et al, 1993;Bertacchini et al, 1999;Francci et al, 1999]. On the other hand, its physicochemical bonding to dentin could have inhibited bacterial percolation through the tooth/restoration interface [Dionysopoulos et al, 1994;ten Cate and van Duinen, 1995;ten Cate et al, 1995;Mertz-Fairhurst et al, 1995;Francci et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Clinical studies have shown an effect of GIC on salivary fluoride levels, 43 acidogenic bacteria 44 and on demineralized dentine restored with GIC and worn in removable appliances. 45 There is anecdotal clinical evidence that secondary caries in association with GIC is at a very low level. This has been supported by one retrospective study, 46 but significantly contradicted by a cross-sectional study, 47 and one five-year prospective study was inconclusive.…”
Section: Fluoride Releasementioning
confidence: 99%
“…3 During the ART procedures, dental hand instruments alone do not remove carious dentin as effectively as rotary burs, and cariogenic bacteria can survive remaining under restorations. [4][5][6] The caries process may progress in the course of time and cause failure of the restoration. 7 This problem may be solved with the use of dental materials that inhibit bacterial growth.…”
Section: Introductionmentioning
confidence: 99%